2022
DOI: 10.1159/000525221
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical AKI and Clinical Outcomes in Elderly Patients Undergoing Cardiac Surgery: Diagnostic Utility of NGAL versus Standard Creatinine Increase Criteria

Abstract: Background: AKI is a common and serious postoperative complication in patients undergoing cardiac surgery and its incidence is particularly high among elderly patients. Cardiac surgery-associated AKI (CSA-AKI) represents the second most common cause of AKI in the intensive care unit but its true incidence could be underestimated, especially in elderly population. The current biomarkers of AKI are unreliable and delayed during acute changes in kidney function. In the setting of subclinical AKI (SAKI), biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In particular, it is well known that BUN, creatinine and hemoglobin levels, and platelet counts are significantly associated with prognosis in elderly patients. [22][23][24][25] A previous study showed similar results to the present study. In the previous study, patients over 50 years of age who visited the emergency room in a coma were classified into 2 groups: a metabolic disorder group and a structural disorder group, and the respective rates were 72% and 28%.…”
Section: Variablessupporting
confidence: 92%
“…In particular, it is well known that BUN, creatinine and hemoglobin levels, and platelet counts are significantly associated with prognosis in elderly patients. [22][23][24][25] A previous study showed similar results to the present study. In the previous study, patients over 50 years of age who visited the emergency room in a coma were classified into 2 groups: a metabolic disorder group and a structural disorder group, and the respective rates were 72% and 28%.…”
Section: Variablessupporting
confidence: 92%
“…The level of p-NGAL appears to be an independent predictor of kidney complications, as well as cardiovascular and liver-related diseases [ 41 43 ]. Overall, p-NGAL has been shown to be the most promising and clinically available kidney injury biomarker and could be used particularly for patients who are critically ill [ 43 , 44 ]. Serum p-NGAL has been found to be a good predictor for AKI and a good predictor of the need for renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings suggest that the overall health of patients with high RDW levels was worse than that of patients with low RDW levels. In particular, it is well known that BUN, creatinine and hemoglobin levels, and platelet counts are signi cantly associated with prognosis in elderly patients [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%